Simplified Roux-en-Y reconstruction after laparoscopic radical distal gastrectomy for gastric cancer - Qian, Yawei; Zhou, Guang; Chang, Feifei; Ping, Xiaochun; Wang, Guoliang (Frontiers in Surgery, 2022)
Background Although there were a variety of strategies for the alimentary tract reconstruction of patients with gastric cancer who underwent laparoscopic radical distal gastrectomy, it remains controversial regarding which procedure is optimal. We developed a simple technique for Roux-en-Y reconstruction during laparoscopic surgery and evaluated its technical feasibility and safety. Methods Seventy-one cases of modified Roux-en-Y reconstructions after laparoscopic radical distal gastrectomy were consecutively performed in our hospital, from November 2020 to March 2022. A retrospective review of medical data was conducted. Intraoperative and postoperative outcomes, including operation time and incidence of postoperative complications, were collected and analyzed. Results All procedures of laparoscopic distal gastrectomy with D2 lymph node dissection were successfully completed without any intraoperative complication. The mean number of retrieved lymph node was 38.8 ± 10.6. Mean operative time was 223.5 ± 42.4 min, whereas intraoperative blood loss was 102.2 ± 96.3 ml. No postoperative mortality was recorded. Six patients (8.5%) experienced postoperative complications and were managed conservatively. In addition, only two patients (2.8%) required rehospitalization during a median short-term follow-up period of 6 months. Conclusions The modified method is a simple and safe approach for laparoscopic radical distal gastrectomy.